Jaws - Spielberg, Steven, 1946-; Scheider, Roy; Shaw, Robert, 1927-1978; Dreyfuss, Richard; Benchley, Peter (Universal City, Calif. : Universal Studios Home Entertainment, 2012)
A great white shark terrorizes a seaside resort town.
Based on the novel by Peter Benchley.
Originally released as a motion picture in 1975.
Features: Spotlight on location : the making of Jaws; digital copy of film; Ultraviolet copy of film.
Roy Scheider, Robert Shaw, Richard Dreyfuss, Lorraine Gary, Murray Hamilton.
MPAA rating: PG.
DVD, Dolby digital 5.1 surround.
Keywords: Benchley, Peter -- Film and video adaptations; Sharks -- Drama; Fiction films; Thriller films; Based on the book; Feature films; Horror films